Designing chemical bonds between active materials and current collectors for packaging a high-performance supercapacitor. (18th December 2019) - Wang, Haoxiang; Yang, He; Wang, Dong; Cheng, Diyi; Deng, Ting; Liu, Hongyan; Zhang, Hengbin; Zhang, Wei; Zheng, Weitao
Abstract: Clarifying the interaction between active materials and current collectors of the same electrode is crucial for understanding the electrochemical energy storage mechanism and designing high-performance supercapacitors. The interaction mechanism is mainly due to the evolution of chemical bonding. Here, we explore the chemical bonding evolution between cobalt-nickel layered double hydroxide and carbon fiber paper by using ex situ x-ray photoelectron spectroscopy during redox reaction. The results reveal that chemical bonding corresponds to more ionic states at the lowest potential and more covalent states at the highest potential. Attributed to the formation of C–O-Metal (Co, Ni) chemical bonds, high capacitance with enhanced stability and rate capability is obtained. The Co–Ni layered double hydroxide electrode exhibits a high areal and mass specific capacitance of 0.55 and 952 F g −1 at a low mass loading of 0.58 mg cm −2 . At a high mass loading of 3.59 mg cm −2, high areal and mass specific capacitance of 3.24 F cm −2 and 811 F g −1 are obtained. Based on this, a hybrid supercapacitor is fabricated with high-mass-loading Co–Ni layered double hydroxide and active carbon as positive and negative electrodes, respectively. As a result, this device delivers a prominent energy density of 20.9 Wh cm −3 at a power density of 0.12 W cm −3 .